Adolescents perception on parent child conflict and its resolution: A qualitative study - Khem Raj Bhatta; Suraj Shakya; Prabin Shrestha (Global Journal of Medicine and Public Health, 2024)
Adolescent period is marked by strain in relationship and misunderstanding